The use of carica papaya leaf juice as a supplement for dengue patients and its potential effect on immune modulation / Maisarah Binti Ab Fatah - Ab Fatah, Maisarah (2014)
Dengue is a major vector-borne disease in Malaysia. Among the symptoms presented in patients with dengue infection are headache, fever, rash, pain behind the eyes as well as muscle and joint pains. Currently, there are no suitable vaccines, specific treatment nor anti-virals for the treatment of dengue. As a result, patients are treated according to symptoms. In Malaysia, the juice of Carica papaya leaves (CPL) has been used as a house-hold remedy for dengue infection. However, there is less scientific evidence to prove this. Thus, this study sought to evaluate the use of CPL juice as a supplement for dengue patients in a designated hospital. CPL juice was given to 50 out of 100 hospitalised patients based on random selection, for three continuous days as a supplement to the existing dengue patient management (termed Intervention (I) group). The remaining 50 patients that solely underwent the standard hospital dengue management were used as the Control (C) group. The serotype of the patients that were recruited was determined in the first part of the study. This was performed by extracting RNA from patient samples (n=100) and subjecting them to real-time PCR using SYBRÂ® Green. Our results shows that the most dominant serotype in I group were DENV-1 (36 %), followed by DENV-2 (22 %), DENV-4 (22 %) and DENV-3 (20 %). In the C group, the most dominant serotype was also DENV-1 with 32 %, followed by DENV-2 (14 %), DENV-3 (14 %) and DENV-4 (6 %). The following part of the work investigates the possible role of CPL juice in modulating immune response of dengue patients. The sera from these patients were subjected to two-dimensional gel electrophoresis (2D-GE) and the respective protein ii profiles were compared using PD Quest 2D Analysis Software. Spots with different altered expression from I and C groups were detected and identified using mass spectrometry. Six proteins were identified to be differentially expressed; four of them were down-regulated and two of them were up-regulated in I group. The down-regulated proteins were vitamin-D binding protein (VDBP), alpha-2-HS glycoprotein (AHSG), clusterin (CLU) and vitronectin (VNR) while the up-regulated proteins were complement C3 (Comp C3) and apolipoprotein C3 (APO C3). Similar pattern of expression was observed when ELISA was performed as a validation step. These proteins are known to be associated with the dengue pathogenesis, except for APO C3. VDBP activates monocytes, stimulates cellular immune response and suppresses immunoglobulin production and lymphocytes proliferation. CLU inhibits the hemolytic activity of the membrane-attack complex of the complement system and the increasing level of this protein has been related to cell death. VNR has also been shown to act as an inhibitor of the cytolytic reactions of the terminal complexes of complement and of perforin. The increased level of Comp C3 assists in removing dengue viral particles and hence influences the antigen-antibody-platelet complex. As a result, less platelet is taken up for the antigen-antibody complex. Our data suggest that CPL juice may exert potential to be used as supplement to aid dengue patientï¿½s recovery.